EFFECT OF WORKLOAD, FAMILY WORK CONFLICT AND WORK STRESS ON EMPLOYEE ORGANIZATIONAL COMMITMENT SAKTI MOBILE LTD - Harries Madiistriyatno; Eric Hermawan (International Journal of Artificial Intelligence Research, 2022)
This research aims to improve employee organizational commitment at Sakti Mobile Ltd by analyzing the direct effect of workload on organizational commitment, the direct effect of work-family conflict on organizational commitment, the direct effect of work stress on organizational commitment, and the simultaneous effect of workload, work-family conflict, and work stress on organizational commitment. This study employs a quantitative strategy and survey methodology. The sample size was 207 individuals. SPSS was used to examine research data gathered through the distribution of questionnaires. The findings revealed that (1) workload has a negative effect on organizational commitment, (2) work-family conflict has a negative effect on organizational commitment, (3) work stress has a negative effect on organizational commitment, and (4) workload, work-family conflict, and work stress all have an effect on organizational commitment. In addition, this study emphasizes the importance of workload, work-family conflict, and work stress on organizational commitment in order to promote organizational commitment.